Untargeted Proteomics-Based Profiling for the Identification of Novel Processing-Induced Protein Modifications in Milk - Meltretter, Jasmin; Wüst, Johannes; Dittrich, Daniel; Lach, Johannes; Ludwig, Jonas; Eichler, Jutta; Pischetsrieder, Monika (Journal of Proteome Research, 2020)
Nonenzymatic post-translational protein modifications (nePTMs) affect the nutritional, physiological, and technological properties of proteins in food and in vivo. In contrast to the usual targeted analyses, the present study determined nePTMs in processed milk in a truly untargeted proteomic approach. Thus, it was possible to determine to which extent known nePTM structures explain protein modifications in processed milk and to detect and identify novel products. The method combined ultrahigh-performance liquid chromatography coupled to electrospray ionization tandem mass spectrometry with bioinformatic data analysis by the software XCMS. The nePTMs detected by untargeted profiling of a β-lactoglobulin-lactose model were incorporated in a sensitive scheduled multiple reaction monitoring method to analyze these modifications in milk samples and to monitor their reaction kinetics during thermal treatment. Additionally, we identified the structures of unknown modifications. Lactosylation, carboxymethylation, formylation of lysine and N-terminus, glycation of arginine, oxidation of methionine, tryptophan, and cysteine, oxidative deamination of N-terminus, and deamidation of asparagine and glutamine were the most important reactions of β-lactoglobulin during milk processing. The isomerization of aspartic acid was observed for the first time in milk products, and N-terminal 4-imidazolidinone was identified as a novel nePTM.
CRIS-Team Scopus Importer:2020-02-18
Keywords: mass spectrometry; processed milk; protein modifications; untargeted profiling; β-lactoglobulin